A Method For Selection of Optimal Conductor in Radial Distribution Network - Paul, Tanvi (My University, 2012)
The demand for electrical energy is ever increasing. Today over 21% (apart from theft) of the total electrical energy generated in India is lost in transmission (4-6%) and distribution (15- 18%). The electrical power deficit in the country is currently about 18%. Clearly, reduction in distribution losses can reduce this deficit significantly. The main reason for having high losses in developing countries like India is stretching of distribution lines beyond the limits of load centres, increase of load abnormally without considering the current carrying capacity of the conductors and imbalance of generation and load causing reactive power generation, etc. The optimal conductor type should be determined for each feeder segment to maintain an acceptable voltage profile along the entire feeders, minimizing capital investments and the cost of feeder losses. The ultimate aim of this thesis work is to plan distribution networks which satisfy the growing demand for electricity, fulfill specific technical operational constraints and which are also characterized by the minimum overall cost and losses. In this Thesis, a method of optimal conductor selection has been proposed based on stability index and the variation of temperature and its effect on resistance has been incorporated. One example of 20-node radial distribution network has been considered. Results shows that the selection of non uniform conductor reduces the losses compared to the uniform conductor. Obviously the planning cost will also be reduced.
M.E. (Power System and Electric Drives)
Keywords: Optimal Conductor; Load Flow; Radial Network